DNA evidence of Trypanosoma cruzi in the Chilean wild vector Mepraia spinolai (Hemiptera: Reduviidae) - Carezza Botto-Mahan; Sylvia Ortiz; Marlene Rozas; Pedro E Cattan; Aldo Solari (Memorias do Instituto Oswaldo Cruz, 2005)
Molecular evidence showed 46.2% of Trypanosoma cruzi infection in Mepraia spinolai insects from North-Central Chile, which is significantly higher than previous reports of up to 26% by microscopic observation. Our results show similar infection levels among nymphal stages, ranging from 38.3 to 54.1%, indicating that younger nymphs could be as important as older ones in parasite transmission. A cautionary note must be stressed to indicate the potential role of M. spinolai in transmitting T. cruzi in country areas due to the high infection level detected by molecular analysis.